(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
The coffee plant can grow together with different plants, but the presence of allelochemicals can affect the crop post-planting. This study aimed to evaluate the early growth of coffee seedlings following treatment with plant extracts from different botanical families. The experimental design used randomized blocks with four trials, in a 7 × 2 factorial scheme; the first factor consisted of aqueous extracts from six species: canola, crotalaria, brachiaria, sunflower, wheat, and lupine; water was used as the control. The second factor comprised of different botanical parts of the aforementioned six species of plant. The extracts were diluted to 5% concentration and were applied at a dose of 20 mL per plant. The agronomic variables analyzed were plant height (PH), stem diameter (SD), leaf area index (LAI), leaf dry matter (LDM), root dry matter (RDM), and root length (RL). Compared to the canola extract, the application of brachiaria extract resulted in the best response in PH, regardless of the botanical part that constituted the extract, leading to an increase in PH by 3.77 cm. The agronomic character most sensitive to the application of aqueous extracts was PH, in which the brachiaria extract was prominent in inducing the greatest growth, whereas the canola extract hindered the initial development of Arabica coffee seedlings.